A model proposal for efficient disaster management: the Turkish sample - (:unkn) unknown (ELSEVIER SCIENCE BV, 2013)
As it is pointed out in the literature, just focusing on disaster response and recovery phases (namely disaster crisis management) and not paying enough care and attention to mitigation and preparedness phases (namely disaster risk management) has caused different problems in Turkey so far. Turkey's experience with disaster management in the last decade is the prime reason for the need to readdress the disaster mitigation problems in terms of developing a better management mechanism in a manner that would provide highest effectiveness and efficiency. This study aims prevent the unnecessary loss of lives and damage to personal and national assets and properties by presenting a suitable and comprehensive disaster management model at strategic level in line with the standards of the United Nations Office for Disaster Risk Reduction. Recurring management problems are presented by the methods of discourse and document analysis. It is seen that the current disaster management mechanism has certain weak parts and after in depth interviews, a new model for an efficient disaster management system is tried to be put forth in the end.
Keywords: Disaster; Disaster Management; Risk Management; Crisis Management